THE INFLUENCE OF THE WORK ENVIRONMENT, WORK MOTIVATION, AND WORK DISCIPLINE ON EMPLOYEE JOB SATISFACTION AT PT. PLN UP3 TANJUNG KARANG INDONESIA - Shella Juan Eriza; Iskandar Ali Alam (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to examine how the environment, motivation, and work discipline affect job satisfaction at PT PLN UP3 Tanjung Karang. This study used a saturated sample which used a total number of employees of 63 people. This study uses quantitative methods and multiple linear regression as data analysis. In the results of the table, the multiple linear regression equation Y = 1.811 + 0.060X1 + 0.522X2 + 0.301X3 is obtained.  The results of the study, namely simultaneously the work environment, work motivation, and work discipline on job satisfaction were calculated F values of 51,771 > table F values of 2,975 and sig values. 0.000 < 0.05, then job satisfaction affects the independent variable. Then, the variables of motivation and discipline have a significant effect, while those that do not have a significant effect are variables on the work environment.